Improving Medical Adherence using Smart Medicine Cabinet Monitoring System - S. A. Ishak; H. Zainol Abidin; M. Muhamad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Patients at home may forget to take their medicines on time, miss doses or even take overdoses. This particularly applies to the elderly at home. Hence, this paper presents a monitoring system to improve the medical adherence which is based on Internet of Things (IoT) concept known as smart medicine cabinet monitoring system.  The system is proposed to remind the elderly to take their medicines on time, to ensure that the elderly have taken their medicines and to notify the family member of the elderly about their medication intake. This paper presents a method of monitoring the medication intake of the elderly which is based on IoT concept to display the data on the web database. The system uses an Arduino microcontroller, a toggle switch, LCD Display, limit switch, alarm system and a Wi-Fi module. The developed system is seen to be another alternative that would help the elderly especially who are living alone for their medication adherence to home-based treatment.